Drivers of Student Performance: Evidence from Higher Secondary Public Schools in Delhi - Deepti Goel; Bidisha Barooah (Global Labor Organization (GLO), 2018)
We examine the role of teachers and students in the formation of grade 12 test scores in public schools in Delhi. There is substantial variation in teacher and student quality within schools. Over the period spanning grades 11 and 12, being taught by a standard deviation better than average teacher raises test scores by 0.373 standard deviation; being a standard deviation better than average student raises it by 0.799 standard deviation. Being tenured positively predicts teacher effectiveness, while educational qualifications, training, experience and personality traits have no predictive power. Relative to families where only fathers earn, those where both parents earn negatively predict student effectiveness, while religion, caste and parents' education have no predictive power. There is some evidence that principals' rating of teachers and value added measures of teacher quality are positively correlated. We recommend teacher compensation be based in-part on ex-post evaluation of value-added measures and principal ratings.
Keywords: I20; I23; 330; Value added; Test scores; Teacher quality; Student quality; India